Estimating the Relative Impacts of Health and Education on Economic Development in Southern Africa - Ganyaupfu, Elvis Munyaradzi (Asian Journal of Economic Modelling, 2014)
This paper analysed the relative impacts of health and education on economic development in Southern Africa. A set of cross country panel data from 11 countries over the period 2005 - 2011 was used in the study. The econometric procedure adopted in the analysis followed the Breusch and Pagan Lagrangian Multiplier test and Hausman test techniques. Based on the Fixed Effects (FE) model, results show that health and education have significant positive effects on economic development; with health having a more remarkable effect on development in the region. The R-squared statistic indicates that nearly 21.79 percent total variation in economic development was accounted for by health and education during the period under review. The F(2,64) statistic (=15.45; p < 0.05) reveals significance of the model; while the interclass correlation value shows that nearly 99.53 percent of the variance was due to differences across panels.